PENGARUH PENGGUNAAN MEDIA MONOPOLI SCIENCE PADA MATERI EKOSISTEM TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Nur Aulia, Fatimah; Septina Rahmawati; Manggalastawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of using "Monopoly Science" media on the learning outcomes of fifth-grade students regarding ecosystem topics. A quantitative approach with a pre-experimental design (One Group Pretest-Posttest) was employed, involving 33 students from SD Muhammadiyah Blimbingrejo as research subjects. Data were collected through validated pretest and posttest instruments, then analyzed using simple linear regression, N-Gain, and Paired Sample T-tests. The results indicated that the Monopoly Science media contributed 62% to student learning outcomes (R2 = 0,620). The N-Gain analysis showed an average score of 0.6039 (moderate category) with an effectiveness level of 60% (fairly effective criterion). Furthermore, the Paired Sample T-test produced a significance value of 0,000 < 0,05, proving a significant difference in learning outcomes as evidenced by the increase in the students' average score from 50.09 to 79.82. In conclusion, the use of Monopoly Science media is proven to be significantly influential and effective in improving the Natural and Social Sciences (IPAS) learning outcomes of elementary school students.